Jonas Aistis as a Lithuanian Decadent - Jurgutienė, Aušra (Colloquia, 2026)
In the history of Lithuanian literature, modernism is primarily associated with the fin de siècle movements of neo-romanticism, symbolism, and the avant-garde. The name of decadent was the most foreign to Lithuanian modernists, although critics, who deemed modernism negatively, used the term most frequently and validated it the most. Only in Bronius Krivickas’s (1919–1952) work “Jonas Aleksandriškis-Aistis’s World of Ideas” (1943), based on academic and aesthetic arguments (Eckart von Sydow’s Die Kultur der Dekadanz, 1921), the poetry of Jonas Aistis (1904–1973), Lithuania’s most European modernist, and the magazine Pjūvis that published poet’s lyrics were considered as belonging to the domain of decadent art. Paradoxically, one must acknowledge that in Lithuania the spirit of decadence flashed most brightly in its own way and in its own time as a gloomy prophecy of the downfall of the individual, nation, and Europe. Before and during WWII, a writer viewed the individual as too weak to overcome an unbearably difficult historical period. The aspect of decadence highlighted in Aistis’s poetry and its connection to patriotism allows the author of this article to discuss more broadly the paradoxical nature of Aistis’s poetry – already examined in Lithuanian literary criticism – and to reveal how characteristic the transformation of cosmopolitan decadence can be in individual national literatures.